COPING WITH LIMITED TECHNOLOGY CONTEXT IN EFL CLASSROOM - Tungka, Novalita Fransisca (Jurnal Bahasa Lingua Scientia, 2013)
The integration of technology into the EFL teaching and learning has become very important since technology can present real life English communication with its complexities into the classroom. This integration has challenged EFL educators to be digitally literate in using technology to support English teaching and learning context. However, problems dealing with technology context in EFL classroom setting such as inaccessible high technology tool, unstable electricity source and unreliable data connection sometimes occur and therefore limit the teaching and learning experience. This paper aims to explore the way of coping with limited technology contexts by carefully selecting and then integrating three most familiar technical tools to the EFL classroom activity namely Facebook, mobile phone and computer, and by manipulating its features to construct the students? learning experiences in both actual and virtual learning environment.